" Analyzing the influence of education quality in Private universities on institutional academic Accreditation Principles through benchmarking: a Comparative study of two Private institutions (Eurasian Journal of History, Geography and Economics, 2023)
The purpose of this study is to investigate the impact and relationship of the quality of private university education on the principles of institutional academic accreditation using (dimensions of reference comparison) as a tool to evaluate, develop, and improve the quality of university performance, through a method of applied and analytical comparative study between two private institutions that were selected to conduct the reference comparison between them. The researchers identified the study objectives, represented in identifying the relationship and impact of the two academic concepts of the quality of educational services with institutional academic accreditation, which each institution seeks to achieve competition and excellence in high performance and its sustainability in its work environment. The questionnaire was used as a primary source for collecting data and information, where (210) questionnaires were distributed to a sample of (university and college presidents and their assistants) and professors of different titles and specializations for both universities to represent the axes of the study variables, with a total of (104) questionnaires for university (AM1), (98) questionnaires for university (BF2) and the stability coefficient reached (98%).Field visits and personal interviews were also conducted, and statistical analysis programs and tools (SPSSV23, EXCELL) were used. The Baron and Kenny (1986) model was chosen in testing the main and subsidiary hypotheses of this type of mediation, and the variables were analyzed using (correlation and explanation coefficient, standard deviation, arithmetic mean, relative importance, coefficient of variation and data analysis by graphs).